2015
DOI: 10.1164/rccm.201410-1765oc
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Human Mesenchymal Stem Cell–derived Microvesicles in Severe Pneumonia in Mice

Abstract: Rationale: Microvesicles (MVs) are anuclear fragments of cells released from the endosomal compartment or shed from surface membranes. We and other investigators demonstrated that MVs released by mesenchymal stem cells (MSCs) were as effective as the cells themselves in inflammatory injuries, such as after endotoxininduced acute lung injury. However, the therapeutic effects of MVs in an infectious model of acute lung injury remain unknown.Objectives: We investigated the effects of human MSC MVs on lung inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
449
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 397 publications
(476 citation statements)
references
References 47 publications
23
449
1
3
Order By: Relevance
“…This is consistent with the literature showing that MSC-derived EVs range from less than 100 nm to 1,000 nm (24,27). Further characterization demonstrated that EVs were more than 90% positive for MSC membrane and more than 90% negative for annexin V and propidium iodide staining, indicating minimal contamination with cell debris or apoptotic bodies and, importantly, that EVs demonstrated uniform expression of CD44 (.98% positive) ( Figure 3A).…”
Section: Msc-derived Evs Expressing Cd44 Are Partially Responsible Fosupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with the literature showing that MSC-derived EVs range from less than 100 nm to 1,000 nm (24,27). Further characterization demonstrated that EVs were more than 90% positive for MSC membrane and more than 90% negative for annexin V and propidium iodide staining, indicating minimal contamination with cell debris or apoptotic bodies and, importantly, that EVs demonstrated uniform expression of CD44 (.98% positive) ( Figure 3A).…”
Section: Msc-derived Evs Expressing Cd44 Are Partially Responsible Fosupporting
confidence: 91%
“…MSCs were able to increase the proportion of phagocytic MDMs in the presence of LPS ( Figure 1D). This adds to the body of literature supporting the phagocytosis-enhancing effects of MSCs on both macrophages and monocytes (8,10,19,27).…”
Section: Msc-derived Ev-treated Murine Amsmentioning
confidence: 63%
See 3 more Smart Citations